Navigating Supply Chain Turbulence Leveraging Modern Technologies for Safety, Resilience, and Risk Reduction. - Żywiołek, Justyna (Productivity Press, 2025)
This book Analyses critical external elements affecting modern logistics, including pandemics, geopolitical conflicts, energy crises, and trade embargoes, and investigates how these circumstances necessitate logistics networks to implement more resilient and adaptable strategies to maintain operational continuity.
Description based upon print version of record.
5.3.5 Amazon's Automation of Warehousing with Robotics and Artificial Intelligence
Keywords: Supply chain management.; Crisis management.; elektronické knihy; electronic books